Starting a Business: A Focus on Construction Permits, Electricity Access, and Property Registration - Hardi, Irsan; Nghiem, Xuan-Hoa; Suwal, Sunil; Ringga, Edi Saputra; Marsellindo, Rio; Idroes, Ghalieb Mutig (Heca Sentra Analitika, 2024)
Efficient processes for construction permits, electricity access, and property registration are critical to fostering entrepreneurship and economic growth. Delays, high costs, and bureaucratic inefficiencies in these areas pose significant barriers to business start-ups. This study examines the impact of these factors on starting a business, highlighting their role in shaping formal economic activity and business dynamics. By applying methods such as the Generalized Linear Model (GLM), Robust Least Squares (RLS), and Quantile Regressions (QR) to data from 213 countries and cities featured in the World Bank’s Doing Business 2019 (DB19) and Doing Business 2020 (DB20) reports, this paper demonstrates that all three factors significantly and positively impact starting a business. Notably, a comparison of results between DB19 and DB20 reveals that the magnitude of these influences decreased in DB20, with some effects becoming less significant or even insignificant compared to DB19. This phenomenon is most apparent in countries with middle-to-high starting a business scores. The findings suggest that shocks like the COVID-19 pandemic may have reduced the relevance of these factors in DB20, as the increased risks associated with starting a business during the pandemic likely overshadowed these considerations. Overall, the results indicate that streamlining construction permits, improving electricity access, and simplifying property registration processes could significantly enhance entrepreneurial activity, drive economic growth, and foster a more dynamic business environment.